MKK4/5-MPK3/6 Cascade Regulates Agrobacterium-Mediated Transformation by Modulating Plant Immunity in Arabidopsis - Liu, Tengfei; Cao, Li; Cheng, Yuanyuan; Ji, Jing; Wei, Yongshu; Wang, Chenchen; Duan, Kaixuan (Frontiers in Plant Science, 2021)
Agrobacterium tumefaciens is a specialized plant pathogen that causes crown gall disease and is commonly used for Agrobacterium-mediated transformation. As a pathogen, Agrobacterium triggers plant immunity, which affects transformation. However, the signaling components and pathways in plant immunity to Agrobacterium remain elusive. We demonstrate that two Arabidopsis MAPKKs MKK4/MKK5 and their downstream MAPKs MPK3/MPK6 play major roles in both Agrobacterium-triggered immunity and Agrobacterium-mediated transformation. Agrobacteria induce MPK3/MPK6 activity and expression of plant defense-response genes at a very early stage. This process is dependent on MKK4/MKK5 function. Loss of function of MKK4 and MKK5 or their downstream MPK3 and MPK6 abolishes plant immunity to agrobacteria and increases transformation frequency, while activation of MKK4 and MKK5 enhances plant immunity and represses transformation. Global transcriptome analysis indicates that agrobacteria induce various plant defense pathways, including ROS production, ethylene and salicylic acid -mediated defense responses, and that MKK4/MKK5 is essential for induction of these pathways. Activation of MKK4 and MKK5 promotes ROS production and cell death during agrobacteria infection. Based on these results, we propose that the MKK4/5-MPK3/6 cascade is an essential signaling pathway regulating Agrobacterium-mediated transformation through modulation of Agrobacterium-triggered plant immunity.